2015
DOI: 10.4236/abc.2015.52010
|View full text |Cite
|
Sign up to set email alerts
|

TNF<i>α</i> and IL1<i>β</i> Stimulate Differential Gene Expression in Endometrial Stromal Cells

Abstract: The purpose of this study was to test the hypothesis that specific macrophage-secreted cytokines cause gene expression changes in endometrial stromal cells that reproduce the effects of macrophages in the development of endometriosis. Telomerase-immortalized human endometrial stromal cells (T-HESC) were treated with tumor necrosis factor α (TNFα, 5 ng/ml) and interleukin 1β (IL1β, 1 ng/ml). Differential expression of 249 genes was identified by DNA microarray. Ontologies such as peptidases, cell adhesion, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…Similar finding was also reported by Chalpe et al. () that telomerase‐immortalized human endometrial stromal cells (T‐HESC) treated with TNF α did not enhance the gene expression of CXCL8/IL8, IL‐1 β , and IL6. TNF α did, however, significantly induce chemokines CCL2, CCL20, CCL5, CX3CL1, and CXCL5 expression in bovine endometrial stromal cells, similar to the results of a study by Liu et al.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar finding was also reported by Chalpe et al. () that telomerase‐immortalized human endometrial stromal cells (T‐HESC) treated with TNF α did not enhance the gene expression of CXCL8/IL8, IL‐1 β , and IL6. TNF α did, however, significantly induce chemokines CCL2, CCL20, CCL5, CX3CL1, and CXCL5 expression in bovine endometrial stromal cells, similar to the results of a study by Liu et al.…”
Section: Discussionsupporting
confidence: 89%
“…; IL1B , and IL6 – Chalpe et al. ), chemokines ( CCL20, CXCL3, CXCL5 – Rossi et al. , and GRO1 – Nasu et al.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, it was demonstrated that some pro-inf lammatory genes including IL-1 and COX-2 can demonstrate a significantly dysregulated expression in some of tissues of endometriosis patients [10,12,[26][27][28]. For instance, Chalpe et al (2015) [26] demonstrated that pro-inf lammatory genes, including IL-1β induce differential expressions in endometrial stromal cells. Our results indicated that MenSCs-CM significantly inhibited the expression of IL-1β and COX-2 in endometriosis cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, it was demonstrated that some pro-in ammatory genes including IL-1 and COX-2 can demonstrate a signi cantly dysregulated expression in some of tissues of endometriosis patients [33,12,[34][35][36]. For instance, Chalpe et al (2015) demonstrated that pro-in ammatory genes, including IL-1β induce differential expressions in endometrial stromal cells [33].…”
Section: Discussionmentioning
confidence: 99%